2022
DOI: 10.3389/fendo.2022.847993
|View full text |Cite
|
Sign up to set email alerts
|

Omicron Variant of SARS-CoV-2 Virus: In Silico Evaluation of the Possible Impact on People Affected by Diabetes Mellitus

Abstract: The Omicron variant of SARS-CoV-2 (Spike mutant B.1.1.529) carrying more than 30-point mutations in its structure, of which 15 are localized in the receptor-binding domain (RBD), allows to hypothesize a relevant change in interactivity with ACE2. In previous reports we hypothesized that the worse outcome of the COVID-19 disease in diabetes mellitus condition could be related to the non-enzymatic glycation of ACE2 receptor and an in silico evaluation led to the demonstration that the number of interactions is d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…On the contrary, SuMD simulations indicate Asn 501 (involved in the N501Y mutation) as one of the most important residues in the recognition process: contrary to other previously mentioned residues, Asn 501 is surrounded by other interacting residues that can be found both in the complex between hACE2 and RBD and in the final state of the SuMD simulation, such as Gln 498, Thr 500 and Tyr 505, which could justify the contained impact of this mutation on the binding affinity of the aptamer compared to the other two. Interestingly, the most recent viral variants of concern include mutations such as Q498R, Y505H, and D405N that increase the positive charge on the spike surface: based on the analysis of the interaction pattern predicted by SuMD (Figure 4 , panel C), all these mutations should increase the affinity with the negatively charged RBD–PB6 RNA aptamer, not only justifying its affinity towards the alpha and beta variant of SARS-CoV-2 but also towards the one from omicron on ( 116 , 117 ). All other geometric and energetic analyses performed on the trajectory are summarized in Supplementary Figures S16–S18 (Supplementary Materials).…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, SuMD simulations indicate Asn 501 (involved in the N501Y mutation) as one of the most important residues in the recognition process: contrary to other previously mentioned residues, Asn 501 is surrounded by other interacting residues that can be found both in the complex between hACE2 and RBD and in the final state of the SuMD simulation, such as Gln 498, Thr 500 and Tyr 505, which could justify the contained impact of this mutation on the binding affinity of the aptamer compared to the other two. Interestingly, the most recent viral variants of concern include mutations such as Q498R, Y505H, and D405N that increase the positive charge on the spike surface: based on the analysis of the interaction pattern predicted by SuMD (Figure 4 , panel C), all these mutations should increase the affinity with the negatively charged RBD–PB6 RNA aptamer, not only justifying its affinity towards the alpha and beta variant of SARS-CoV-2 but also towards the one from omicron on ( 116 , 117 ). All other geometric and energetic analyses performed on the trajectory are summarized in Supplementary Figures S16–S18 (Supplementary Materials).…”
Section: Resultsmentioning
confidence: 99%
“…Increased morbidity among patients with diabetes mellitus has been observed since the onset of the pandemic [ 38 , 39 ]. However, the underlying reasons for this phenomenon remain a subject of debate [ 40 ]. Bassani et al recently reported findings suggesting that the Omicron variant exhibits a higher affinity between the viral Spike protein and the human receptor ACE2.…”
Section: Discussionmentioning
confidence: 99%
“…The computational analysis results allow us to hypothesize that affinity between the viral protein Spike and the human receptor ACE2 is 3. Odds ratios estimates with corresponding 95% CI's for predictors included to the model higher for the omicron variant concerning the wild-type SARS-CoV-2 both in native conditions and also in the case of non-enzymatic glycation, typical of the hyperglycaemic environment [16].…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 diabetes mellitus (T2D) is equally common in patients with delta and omicron strains [14], but the possible occurrence of alternative ways of virus entry in people affected by diabetes, as recently suggested [15], makes the new omicron virus mutation of particular interest in patients with diabetes. Whether this new variant may influen ce the real-world clinical evolution of COVID-19 in people affected by diabetes mellitus is still a matter of speculation [16].…”
Section: Introductionmentioning
confidence: 99%